Logística reversa, legislação e sustentabilidade: um modelo de coleta de óleo de fritura residual como matéria-prima para produção de biodiesel - Lago, Sandra Mara Stocker (2013)
This study aimed to propose a sustainable and optimized model of residual frying oil collection as raw material for the production of biodiesel from educational establishments, in accordance with current legislation. A process of collecting waste frying oil involves different steps, with a large number of participants, and should involve the society as a whole, so we carried out interviews with the main social performers that may be involved in supporting this process in the city of Cascavel, West of Paraná. The use of public education institutions that have Elementary School II as collection point is important, because it involves children and teenagers who are in training for the development of environmental awareness and they can be the disseminators of this culture in their familiar surroundings, resulting in the extension of the project to the whole community. In addition to the environmental gains, the economic gains can also be achieved with the sale of the waste for processing into biodiesel through Parents, Teachers, and Employees Associations (APTEs), which may apply the resources to improve teaching conditions. However, despite the potential benefits for the use of this waste it is highlighted the lack of specific laws and federal incentives for the use of this raw material for biodiesel production. Some incentive Laws at the state and municipal level were identified, however, a federal law would surely drive these actions in Brazil. It was also possible to identify that one way to reduce the cost of biodiesel produced from waste frying oil, which has been dispersed in urban areas, is using an optimized route collection and waste transport. Through the reverse logistics of waste frying oil, it is possible to conclude that sustainability, besides the application of effective legislation and the collection route optimization for cost reduction, makes up the conditions for the creation of a program of collecting waste frying oil for biodiesel production, in addition to the involvement of society, which is constituted as a source of generating waste and can also become the indirect beneficiary of a project like this.